2018
DOI: 10.1007/s13244-018-0639-9
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural networks: an overview and application in radiology

Abstract: Convolutional neural network (CNN), a class of artificial neural networks that has become dominant in various computer vision tasks, is attracting interest across a variety of domains, including radiology. CNN is designed to automatically and adaptively learn spatial hierarchies of features through backpropagation by using multiple building blocks, such as convolution layers, pooling layers, and fully connected layers. This review article offers a perspective on the basic concepts of CNN and its application to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1,951
0
60

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,337 publications
(2,015 citation statements)
references
References 43 publications
4
1,951
0
60
Order By: Relevance
“…Also, another work based on deep learning techniques with an interpretable visual output, identified that the regions surrounding the nodule were the most relevant for the classification decision 18,31 . In our opinion, it is crucial to emphasise this characteristic, as it might change the direction and broaden the analysis spectrum of future radiogenomics studies, which until now have been mainly focusing on the nodule or in a region of interest (ROI) around it [32][33][34] . Lung cancer is the result of multiple and complex combinations of morphological, molecular and genetic alterations 35 .…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Also, another work based on deep learning techniques with an interpretable visual output, identified that the regions surrounding the nodule were the most relevant for the classification decision 18,31 . In our opinion, it is crucial to emphasise this characteristic, as it might change the direction and broaden the analysis spectrum of future radiogenomics studies, which until now have been mainly focusing on the nodule or in a region of interest (ROI) around it [32][33][34] . Lung cancer is the result of multiple and complex combinations of morphological, molecular and genetic alterations 35 .…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Deep-learning models have been particularly effective in image analysis, mainly in radiology. 49 A deep-learning model can learn to classify images as healthy or diseased or can notate the areas in the image that correspond to organs or other anatomic structures. For example, a deep-learning model was able to identify the segmentation of white matter, gray matter, and cerebrospinal fluid in the brains of babies.…”
Section: Medical Image Analysismentioning
confidence: 99%
“…In every network layer, there can be a number of different convolution steps resulting in different feature maps. To the output of the convolution, a nonlinear activation function is applied, here, the most common function is the rectified linear unit (ReLU) operation, which is : truef(x)=normalmax(0,x) …”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…This can be overcome by padding the edges with an extra layer. [5] The kernels are the learnable parameter in this operation and are adapted in the training of the network. In every network layer, there can be a number of different convolution steps resulting in different feature maps.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation